Near-surface characteristics of velocity profile and momentum transport after wave-breaking in deep water. (15th May 2023) - Xue, Qingren; Liang, Shuxiu; Sun, Zhaochen; Xu, Yuanyuan; Tian, Zirui
Abstract: Wave-breaking plays an important role in the process of mixing in the upper ocean, which can cause wave momentum and energy flux loss, enhance near-surface turbulence, and adjust the distribution of the momentum flux at the air-sea interface. In this paper, wave-breaking was generated using a laboratory method of controllable deep water breaking waves, and flow field characteristics after wave-breaking were measured and analyzed using PIV technology and the ensemble average method. The velocity threshold was proposed for the effective influence of wave-breaking on the flow field, then the EID (Effective-Influenced-Depth) of wave-breaking, which is D v in the paper, was quantified, and the quantitative relationship between D v and energy loss induced by breaking was established. Velocity characteristics of the near-surface flow field and transport characteristics of horizontal momentum induced by wave-breaking were analyzed, which can contribute to the parameterization of wave-breaking. The results show that the energy injected by wave-breaking is transported downstream along the direction of wave propagation. The vertical-influenced range of wave-breaking is about 1–2 times the wave-breaking height. The time integral of horizontal momentum flux increases significantly in the depth of about 1 time the wave-breaking height near the surface and decays significantly with depth. Mass transport of the fluid near the surface induced by wave-breaking mainly occurs in the depth where momentum flux increases significantly. After about 29 times the SWWP (spectrally weighted wave period) after breaking, fluid near the surface is no longer under the action of horizontal stress induced by wave-breaking, so no mass transport occurs anymore. For parameterization of wave-breaking in circulation models, the research can provide a reference in time and space scale, as well as experimental data support for the establishment of a new influence mode. Highlights: Laboratory generation method of controllable deep water breaking waves is proposed to generate the wave train with single breakage so that obvious characteristics of the flow field can be obtained. The effective-influenced depth (EID) of wave-breaking is quantified based on the velocity threshold V t h d and velocity profiles in the near-surface flow field are presented. Characteristics of horizontal momentum transport near the surface after wave-breaking are obtained and the time integral of the horizontal momentum flux along the cross-section is presented in figures. The time accumulated value of the vertical integral of the horizontal momentum flux under breaking and nonbreaking conditions are presented in figures. Then a horizontal force acting on the water body can be recognized from the figures during the breaking process.